Deploying cloud technologies Office 365 in financial institutions - Vokoun, Jan (2015)
This bachelor's thesis deals with deploying cloud-based services Office 365, namely in the financial institution Komerční banka, a.s. The aim of this thesis is to create a list of problematic aspects which complicate deploying cloud-based services Office 365 in Komerční banka, a.s. This thesis is divided into four chapters. The first one explains the cloud computing concept, its characteristics and models. The second chapter presents the Office 365 product and its services. The third part describes the strategy for their deployment and the last chapter is dedicated to actual process of their implementation in Komerční banka, a.s.